Scenario Thinking-Based Strategy in Preventing Sexual Violence in Higher Education: Strategic Learning from Universitas Brawijaya - Said, Moh; Cahyasari, Erlita; Pratama, Bayu Indra; Hidayat, Cikal Azahra Putri; Kubebity, Latisha Nazahira (Universitas Medan Area, 2025)
Sexual violence has been a public concern, and cases of sexual violence in Indonesia have been increasing in recent years. The cases also occur in higher education, which should be a strong fortress against moral damage. The phenomenon of sexual violence is something that is both visible and invisible and difficult to control. A competent strategy is required for higher education to prevent sexual violence. This study aims to describe the preventive strategies adopted by Universitas Brawijaya to address sexual violence on campus through a scenario thinking approach. A qualitative method was employed, comprising five phases: orientation, monitoring, action, synthesis, and exploration. The findings reveal that the university's strategy focuses on identifying potential risks, conducting risk analysis, simulations, and implementing multi-stakeholder-based interventions. Key components include the development of institutional policies, the establishment of dedicated units such as the Integrated Unit for Sexual Violence and Bullying and the Ethics Commission, and the active involvement of student organizations and academic communities. The study concludes that a comprehensive, adaptive, and collaborative approach is essential for universities to effectively prevent and manage sexual violence in a dynamic and uncertain environment.